Praktik Penyelesaian Sengketa di Pengadilan Agama Melalui Sidang Keliling Dikaitkan dengan Prinsip dan Asas Hukum Acara Perdata - Kusmayanti, Hazar; Putri, Sherly Ayuna; Rahmainy, Linda (ADHAPER: Jurnal Hukum Acara Perdata, 2018)
The religious court through the mobile court made a breakthrough in applying the principle of cheap, simple and fast in the proceedings. The circuit assembly is carried out to fulï¬ ll the justice of the community especially those who are lawless and live on the edge of the city. This research is intended to ï¬nd out the practice of conducting a circuit court in religious courts whether it is in accordance with the principles and legal principles of civil procedure. The method used is normative juridical which focuses on research into applicable legal provisions, namely Law No. 48 of 2009 concerning Judicial Power, Het Herziene Indonesisch Reglement or HIR and Perma No.1 of 2015. The speciï¬ cation of this study is descriptive analytical then analyzed using qualitative normative methods. Based on the research conducted that the practice of mobile courts conducted in the Religious Courts is in accordance with the principles and principles of civil procedural law as stated in, Het Herziene Indonesisch Reglement or HIR and the implementation process is in accordance with Perma No.1 of 2015 concerning Integrated Session Services Around the District Court and Religious Court/Syarâ€™iyah Court in Order to Issue Marriage Deed, Marriage Book, and Marriage Certiï¬cate